Evaluate the effect of mutans Aspergillus niger to the nutritive value of fermentation at coconut meal and karnel palm meal (Biodiversitas Journal of Biological Diversity, 2016)
Agricultural wastes, such as coconut meal and kernel palm meal can be used to fulfill the need of feed for ruminants ormonogastrics. Fermentation technology using Aspergillus niger has been reported allow to increase their nutritive value.Isolation of the asporogenous strain which could spored at room temperature but could not spored at 37oC is expected to sole the fermentation of spores in the fermentation product. The spore formation of mutants at the fourth day incubationtime (10%) was less than the wild type (100%). The variance analysis of protein content in vitro Dry Matter Digestibility (IVDMD) and in vitro Protein Digestibility (IVPD) showed that the kind of mutants were interacted with the incubation time(P